Community Control of Hypertension and Diabetes (CoCo-HD) program in the Indian states of Kerala and Tamil Nadu: a study protocol for a type 3 hybrid trial - Ganeshkumar Parasuraman; Panniyammakal Jeemon; Kavumpurathu R. Thankappan; Mohammed K. Ali; Ajay Mahal; Barbara McPake; John Chambers; Pilvikki Absetz; Sathish Thirunavukkarasu; Abdul Majeed Nabil; Selvarajan Valsa Shiby Kripa; Parambilan Kandi Akshay; et al. (BMC, 2024)
Abstract Introduction India grapples with a formidable health challenge, with an estimated 315 million adults afflicted with hypertension and 100 million living with diabetes mellitus. Alarming statistics reveal rates for poor treatment and control of hypertension and diabetes. In response to these pressing needs, the Community Control of Hypertension and Diabetes (CoCo-HD) program aims to implement structured lifestyle interventions at scale in the southern Indian states of Kerala and Tamil Nadu. Aims This research is designed to evaluate the implementation outcomes of peer support programs and community mobilisation strategies in overcoming barriers and maximising enablers for effective diabetes and hypertension prevention and control. Furthermore, it will identify contextual factors that influence intervention scalability and it will also evaluate the program's value and return on investment through economic evaluation. Methods The CoCo-HD program is underpinned by a longstanding collaborative effort, engaging stakeholders to co-design comprehensive solutions that will be scalable in the two states. This entails equipping community health workers with tailored training and fostering community engagement, with a primary focus on leveraging peer supportat scale in these communities. The evaluation will undertake a hybrid type III trial in, Kerala and Tamil Nadu states, guided by the Institute for Health Improvement framework. The evaluation framework is underpinned by the application of three frameworks, RE-AIM, Normalisation Process Theory, and the Consolidated Framework for Implementation Research. Evaluation metrics include clinical outcomes: diabetes and hypertension control rates, as well as behavioural, physical, and biochemical measurements and treatment adherence. Discussion The anticipated outcomes of this study hold immense promise, offering important learnings into effective scaling up of lifestyle interventions for hypertension and diabetes control in low- and middle-income countries (LMICs). By identifying effective implementation strategies and contextual determinants, this research has the potential to lead to important changes in healthcare delivery systems. Conclusions The project will provide valuable evidence for the scaling-up of structured lifestyle interventions within the healthcare systems of Kerala and Tamil Nadu, thus facilitating their future adaptation to diverse settings in India and other LMICs.